The Effects of Mutual Trustworthiness between Labour and Management in Adopting High Performance Work Systems - Yoon-Ho, Kim; Dong-One, Kim; Ali, Mohammad (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2015)
In this study, we examine the role of mutual trustworthiness between labour representatives and management and its relationship with the adoption of High Performance Work Systems (HPWS) in the Korean employment relations context. We argue that trustworthiness is a feature of the parties to the exchange, as opposed to trust, which explains the nature of exchange relationships. We follow existing literature on trustworthiness and agree that it is composed of three variables, i.e., ability, integrity, and benevolence. We test the effects of these three variables as important antecedents for the adoption of HPWS at the workplace level. Using the National Establishment Survey 2009 conducted by Statistics Korea as a sample frame, we survey a representative sample of Korean establishments. These data consist of 1,353 paired responses from labour representatives and managers.Our results show that labour-management mutual ability trustworthiness (MAT) has a positive and significant relationship with the adoption of high performance work systems ( Hypothesis 1 ); mutual benevolence trustworthiness (MBT) has a positive and significant relationship with the adoption of high performance work systems ( Hypothesis 2 ); and mutual integrity trustworthiness (MIT) has a positive and significant relationship with the adoption of high performance work systems ( Hypothesis 3 ). These results show that mutual trustworthiness in Korean employment relations is an important antecedent for the adoption of HPWS and can enable Korean industry to improve its position in the global economy. In the final analysis, it is implied that employment relations actors pursuing cooperative employment practices should ensure the development of a virtuous cycle of mutual trustworthiness.